Overheard and Observed: Horizontal Surveillance in Austen and Edgeworth - Thompson, Lucy E. (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2026)
This article examines how early nineteenth-century British novels employed horizontal surveillance—peer-based observation—to regulate women’s behavior and reinforce social norms. Focusing on Jane Austen’s Sense and Sensibility (1833 [1811]) and Maria Edgeworth’s Belinda (1824 [1801]), it explores how different sensory modes of scrutiny—auditory in Austen’s world of whispered speculation, gossip, and overhearing, and visual in Edgeworth’s depiction of public spectacle—converge to produce a rich vocabulary of social control. Although separated by distinct social milieus, both authors responded to the shifting cultures of surveillance in the Romantic period, forging literary frameworks that anticipate both Victorian social policing and our own era’s digitally mediated modes of communal monitoring. Austen’s Marianne Dashwood and Edgeworth’s Harriet Freke emerge as instructive figures: Marianne’s emotional openness and Harriet’s nonconformity each invite intense scrutiny, compelling them and those around them to internalize regulatory norms. However, both also enact forms of resistance: one rooted in sincerity, the other in performance and defiance. As the 250th anniversary of Austen’s birth occurred in December 2025, re-examining these novels through surveillance theory highlights their continued relevance. These novels illuminate how informal systems of social control operated across time and how women’s responses to surveillance can be both constrained and strategic.